The Influence of Flood Disaster Management Education on The Level of Knowledge Nurses at Limboto Barat Community Health Center - Pipin Yunus; Hamna Vonny Lasanuddin; Sri Vidyanti S. Moha (Poltekkes Kemenkes Palu, 2025)
Background: Adequate knowledge of flood disaster management among nurses is essential to support preparedness and effective response in primary healthcare settings. This study examined the effect of flood disaster management education on nurses’ knowledge at the Limboto Barat Community Health Center. Methods: A quasi-experimental one-group pretest–posttest design was conducted among 20 nurses recruited through purposive sampling. The intervention comprised two 90-minute educational sessions delivered over two consecutive days using lectures, group discussions, and audiovisual media. Knowledge was measured using a validated 20-item multiple-choice questionnaire (Cronbach’s α = 0.82). Pre- and post-intervention scores were compared using a paired-sample t-test with p < 0.05. Results: Mean knowledge scores increased significantly after the intervention (pretest 11.10 ± 2.10 vs posttest 13.55 ± 2.00; mean difference 2.45; p < 0.001). The proportion of nurses categorized as having good knowledge increased from 20.0% to 50.0%, while poor knowledge decreased from 35.0% to 15.0%. Conclusion: Flood disaster management education significantly improved nurses’ knowledge at the Limboto Barat Community Health Center. Further studies with larger samples and controlled designs are recommended to strengthen generalizability and assess longer-term retention.